Modular sintering machine exhaust -heat boiler - LI GUANGYAO; PAN HAI; CAO YONG; CHENG HAIQUAN; ZHANG YINGCHUN; JIANG GUANGCONG; LI YING; CHEN DUN; LU ZILONG; YUAN KE (2016)
The utility model discloses a modular sintering machine exhaust -heat boiler, including the import flue, the water heater module receives hot side flue, exhaust pass, disposed upright flue, steelframe and digital pulse soot blower. The beneficial effects of the utility model are that modular sintering machine exhaust -heat boiler sets up the wind discharge flue of extricating oneself, realizes natural draft, and the box leakproofness is strong, compact structure, and on -the -spot simple to operate is swift, has saved the time limit for a project, has reduced construction cost. 本实用新型公开了种模块式烧结机余热锅炉，包括进口烟道，热水器模块，受热面烟道、出口烟道，直置烟道，钢架和数字式脉冲吹灰装置。本实用新型的有益效果是模块式烧结机余热锅炉设置自拔风排烟道，实现自然通风，箱体密封性强，结构紧凑，现场安装方便快捷，节省了工期，降低了施工成本。